To create a perfect square trinomial, halve the x coefficient, square it, and then add that value.
In the case of x² + 6x, we would have 6 to get 3, then square 3 to get 9.
We would add 9 to make a perfect square trinomial.
<u>
</u><u>Why this works</u>
A perfect square trinomial is designed to factor to some value (x+n)².
When you FOIL this you get x² + 2nx + n².
As you can see, if you wanted to find the value of that n², you could take that x coefficient 2n, halve it to get n, and then square it to get n²!
Answer:
Option A.
Step-by-step explanation:
we have
![x+\frac{b}{2a} =\pm\sqrt{\frac{b^2-4ac}{4a^2}}](https://tex.z-dn.net/?f=x%2B%5Cfrac%7Bb%7D%7B2a%7D%20%3D%5Cpm%5Csqrt%7B%5Cfrac%7Bb%5E2-4ac%7D%7B4a%5E2%7D%7D)
Simplify the right side of the equation
we know that
![\pm\sqrt{\frac{b^2-4ac}{4a^2}}=\pm\frac{\sqrt{b^2-4ac}}{\sqrt{4a^2}}=\pm\frac{\sqrt{b^2-4ac}}{2a}](https://tex.z-dn.net/?f=%5Cpm%5Csqrt%7B%5Cfrac%7Bb%5E2-4ac%7D%7B4a%5E2%7D%7D%3D%5Cpm%5Cfrac%7B%5Csqrt%7Bb%5E2-4ac%7D%7D%7B%5Csqrt%7B4a%5E2%7D%7D%3D%5Cpm%5Cfrac%7B%5Csqrt%7Bb%5E2-4ac%7D%7D%7B2a%7D)
so
The expression is
![x+\frac{b}{2a}=\pm\frac{\sqrt{b^2-4ac}}{2a}](https://tex.z-dn.net/?f=x%2B%5Cfrac%7Bb%7D%7B2a%7D%3D%5Cpm%5Cfrac%7B%5Csqrt%7Bb%5E2-4ac%7D%7D%7B2a%7D)
therefore
x plus b over 2 times a equals plus or minus the square root of b squared minus 4 times a times c, all over 2 times a
Answer:
167.46
Step-by-step explanation:
![V=\frac{1}{3} X \pi r^{2} X h](https://tex.z-dn.net/?f=V%3D%5Cfrac%7B1%7D%7B3%7D%20X%20%20%5Cpi%20r%5E%7B2%7D%20X%20h)
![\frac{1}{3} x 3.14 x 4^{2} x10](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B3%7D%20x%20%203.14%20x%204%5E%7B2%7D%20x10)
![\frac{1}{3} X 50.24x 10](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B3%7D%20X%2050.24x%2010)
![\frac{1}{3} x 502.4](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B3%7D%20x%20502.4)
![V=167.46](https://tex.z-dn.net/?f=V%3D167.46)